Yeager’s Raiders - Jim Hoy (Symphony in the Flint Hills, 2016)
William Least Heat-Moon, in PrairyErth, mentions a bit of Civil War action that occurred very near the site of this year’s Symphony in the Flint Hills.
Keywords: Elisha Mardin; ranch; Palenske feed yard; Santa Fe Trail; bushwhackers; Confederate; Civil War; OLD BANK WITH SANDRA’S DOG; ELMDALE; Mark A. Fisher